A Biblical Review of the "Bank Emok" Business Practiced by Believers - Erlyna Erlyna; Yanto Paulus Hermanto; Ferry Simanjuntak (Asian Journal of Philosophy and Religion, 2026)
This study examines the compatibility of this practice with biblical teachings and its implications for the spiritual lives of believers. Christian participation in this system creates moral dilemmas and damages the church's prophetic witness. Using a qualitative, library-based theological-normative approach, the research analyzes biblical texts, theological literature on usury and professional ethics, and empirical studies on Bank Emok. Findings indicate that high-interest lending directed at the poor contradicts Scripture's consistent emphasis on justice, compassion, and protection for the vulnerable (Exod. 22:25; Lev. 25:36–37; Luke 6:34–35). Through Watchman Nee's framework of occupational ethics, Bank Emok is classified as a "pure trader" enterprise that transfers rather than creates wealth rendering it theologically problematic for believers.